2004
DOI: 10.1107/s0907444904028173
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a yellow lupin pathogenesis-related PR-10 protein belonging to a novel subclass

Abstract: Pathogenesis-related (PR) proteins of class 10 are abundant in higher plants. Some of these proteins are induced under stress conditions as part of the plant defence mechanism. Other homologues are developmentally regulated and their expression varies in different plant organs. The PR-10 proteins are encoded by multigene families, have a weight of about 17 kDa and are found in the cytosol. In yellow lupin, nine different homologues have been identified and divided into two subclasses, LlPR-10.1 and LlPR-10.2. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
52
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 49 publications
1
52
1
Order By: Relevance
“…For instance, ANS (8-anilino-1-naphthalenesulfonic acid) displacement assays revealed that a birch (Betula verrucosa) pollen PR-10 protein (Betv1) may bind many physiologically relevant ligands (Mogensen et al, 2002). It has been suggested that the ligand binding function of PR-10 proteins might be controlled by the sequence and conformation of helix a3 (Pasternak et al, 2005). In agreement with these speculations is the observation (A) Selected purine-and urea-type cytokinins.…”
Section: Introductionsupporting
confidence: 63%
See 3 more Smart Citations
“…For instance, ANS (8-anilino-1-naphthalenesulfonic acid) displacement assays revealed that a birch (Betula verrucosa) pollen PR-10 protein (Betv1) may bind many physiologically relevant ligands (Mogensen et al, 2002). It has been suggested that the ligand binding function of PR-10 proteins might be controlled by the sequence and conformation of helix a3 (Pasternak et al, 2005). In agreement with these speculations is the observation (A) Selected purine-and urea-type cytokinins.…”
Section: Introductionsupporting
confidence: 63%
“…Helix a3 is generally the most diverse fragment also among classic PR-10 proteins (Biesiadka et al, 2002). The helices differ not only in conformation, with the most drastic example furnished by Lupinus luteus (Ll) PR-10.2A, in which the helix is kinked by 608 (Pasternak et al, 2005), but also in position, as in Betv1, in which the entire helix is shifted about one coil along its axis. It has been postulated that the variability of helix a3 has evolved as a way of regulating the specificity of the numerous PR-10 proteins toward their ligands through changes in the volume and shape of the binding cavity.…”
Section: Csbp and The Pr-10 Protein Familymentioning
confidence: 99%
See 2 more Smart Citations
“…This is revealed by the structures of a number of PR-10 proteins obtained by NMR and x-ray crystallography, such as Bet v 1 from birch (Betula spp. ; Gajhede et al, 1996;Markovic-Housley et al, 2003), four isoforms of LlPR10 from yellow lupin (Lupinus luteus; Biesiadka et al, 2002;Pasternak et al, 2005;Fernandes et al, 2008), VrCSBP (cytokininspecific binding protein) from mung bean (Vigna radiata; Pasternak et al, 2006), Pru av 1 from cherry (Prunus avium; Neudecker et al, 2001), and Ap g 1 from celery (Apium graveolens; Schirmer et al, 2005).…”
mentioning
confidence: 99%